1999
DOI: 10.1007/bf03161688
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of wetland hydrology using hydrogeomorphic classification

Abstract: Hydrologic data are essential for understanding relationships between wetland morphology and function and for characterizing landscapeTscale patterns of wetland occurrence. We monitored water levels in 45 wetlands for three years to characterize the hydrology of wetlands in the vicinity of Portland, Oregon, USA and classified wetlands by hydrogeomorphic (HGM) class to determine whether hydrologic regimes differed in wetlands in different HGM classes. We also compared hydrologic regimes in naturally occurring w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 12 publications
0
34
0
Order By: Relevance
“…There has been some work using HGM to organize and understand wetland function, most notably hydrology (e.g., Shaffer et al 1999;Cole and Brooks 2000), and stressors such as sedimentation (Wardrop and Brooks 1998), but there have been few empirical studies investigating functional differences between HGM classes. For HGM to be most useful as a classification tool, it is critical for wetland managers to have the ability to derive some understanding of wetland function based on a wetland's designation into a subclass (Cole et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…There has been some work using HGM to organize and understand wetland function, most notably hydrology (e.g., Shaffer et al 1999;Cole and Brooks 2000), and stressors such as sedimentation (Wardrop and Brooks 1998), but there have been few empirical studies investigating functional differences between HGM classes. For HGM to be most useful as a classification tool, it is critical for wetland managers to have the ability to derive some understanding of wetland function based on a wetland's designation into a subclass (Cole et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers in New England (e.g., Windmiller 1996) have suggested a positive relationship between pond size and hydroperiod, but research conducted elsewhere in the United States has shown the correlation to be weak (Snodgrass et al 2000a) or nonexistent (Shaffer et al 1999;Babbitt and Tanner 2000). In central Massachusetts, Brooks and Hayashi (2002) found that pond area, depth, and volume individually explained less than one-third of the variation in hydroperiod (r ranged from 0.45 to 0.58).…”
Section: Introductionmentioning
confidence: 99%
“…The low similarity produced by the LLWW system agrees with findings of other investigations (cf. Shaffer et al 1999). Although Cole et al (1997Cole et al ( , 2002 found similarities in hydrological conditions among flow-path classes within the state of Pennsylvania (USA), within-class similarity was low when the classes were extended across a wider region (Cole et al 2008), or applied across the continent in the state of Oregon (Cole and Brooks 2000).…”
Section: Discussionmentioning
confidence: 99%